(untitled) (Research, Society and Development, 2021)
This article aims to assess the frequency of common mental disorder (CMD) among undergraduate students at a military training school, according to sociodemographic characteristics and behavioral aspects. The study was carried out in 2020, with 194 students between 17 and 25 years of age at a Merchant Marine officers training school (EFOMM). The reduced version of the General Health Questionnaire (GHQ-12) was used to assess the presence of CMD. Data analysis showed that CMDs are present in 71.1% of participating students, with a higher frequency among young women, second year students, older, non-white students (brown, black and yellow), low socioeconomic status, non-heterosexuals and those who are most influenced by faith. The results of this study can help to identify more vulnerable subgroups, in addition to creating more focused prevention and management measures in the university environment.